ANALISIS DEBIT AIR DI DAERAH TANGKAPAN AIR (DTA) BARABAI KABUPATEN HULU SUNGAI TENGAH - Noraito Gultom; Badaruddin Badaruddin; Syarifuddin Kadir (Universitas Lambung Mangkurat, 2022)
Water discharge is the rate of water flow in a river channel in a certain volume per unit time. This study aims to analyze water discharge and water level, analyze the relationship between water discharge and water level in the Barabai catchment area, Hulu Sungai Tengah Regency. Measurement of water discharge is done using the float method. The resulst obtained at the first point mean that the water discharge is 17.31 m3/second with an average water level of 1 m. At the second point the average water discharge is 15.43 m3/second with an average water level of 0.98 m. At the third point the average water discharge is 16.61 m3/second with an average water level of 0.46 m. The relationship between water discharge and water level at the first point is 0.9835, the second point is 0.9969, and at the third point is 0.9948, which means that the three have a very strong correlationDebit air merupakan laju aliran air pada saluran sungai dalam volume persatuan waktu tertentu. Penelitian ini bertujuan untuk menganalisis debit air dan tinggi muka air, menganalisis hubungan antara debit air dan tinggi muka air di DTA Barabai Kabupaten Hulu Sungai Tengah. Pengukuran debit air dilakukan dengan menggunakan metode pelampung. Hasil yang diperoleh pada titik pertama rata-rata debit air 17,31 m3/detik dengan tingi muka air rata-rata 1 m. Pada titik kedua rata-rata debit air 15,43 m3/detik dengan tinggi muka air rata-rata 0,98 m. Pada titik ketiga rata-rata debit air 16,61 m3/detik dengan tinggi muka air rata-rata 0,46 m. Hubungan debit air dengan tinggi muka air pada titik pertama adalah 0,9835, titik kedua adalah 0,9969, dan pada titik ketiga adalah 0,9948 yang berarti ketiganya memiliki korelasi yang sangat kuat.